The Effect of Working Environment, Trust in Management, and Job Satisfaction - Jeyhan, Rahmat Berliano (APPS Publications, 2022)
ABSTRACT Objective – This study was conducted to identify the relationship between working environment, trust in management, and job satisfaction toward employee loyalty among millennial employees. Methodology – Quantitative method was applied for this data analysis research. The study objective is accepted with the use of SPSS 25.0 in processing the data. Findings – The empirical result showed that working environment and trust in management directly and significantly affect employee loyalty among millennials. In contrast, job satisfaction is shown to have no significant effect on employee loyalty. Novelty – This is one of the first studies to examine trust in management concerning employee loyalty context in Indonesia, and in particular, the joint influence of working environment and job satisfaction. Keywords: employee loyalty, trust in management, working environment, job satisfaction JEL Classification: J28, M1, M10, M12, Article Info: Received 21 January 2022. Accepted 21 July 2022 Article Correspondence: rahmat.jeyhan@my.sampoernauniversity.ac.id Recommended Citation: Jeyhan, Rahmat B. (2022), The Effect of Working Environment, Trust in Management, and Job Satisfaction. Journal of Multidisciplinary Issues 2(1) 1-9 (2022)